Analysis of Mathematics Literacy Ability in Solving PISA-type Questions viewed from Students’ Mathematical Disposition - Dimas Hudda Satriani; Yuyu Yuhana; Etika Khaerunnisa (Study Program of Mathematics Education of Unimed Postgraduate Program, 2023)
The purpose of this research intended to described the qualities of students' mathematical dispositions and mathematical literacy in response to PISA-style questions. This research uses qualitative approaches and also incorporated within the qualitative descriptive research. The 39 students in class 10 MIPA who participated in the research were then reduced to three students to represent the low, medium, and high levels of disposition. The data were gathered using a questionnaire that measures students' mathematical disposition, a written essay test that measures students' mathematical literacy, and direct interviews. The outcome revealed that five students fell into the low mathematical disposition category, 25 students had medium mathematical disposition, and nine students had high mathematical disposition. On the PISA scale of mathematical literacy, students with low mathematical disposition earn level 2, students with medium mathematical dsiposition achieved level 4 whereas those with strong mathematical disposition obtain level 6.